Kewajiban Pemberian Vaksin Corona Virus Disease 2019 (COVID-19) Berkaitan Dengan Hak Otonomi Pasien - Ervina Dita Harnika Putri (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe outbreak of the Corona Virus Disease 2019 (COVID-19) caused various impacts on the sectors of life. One of the efforts is the implementation of the COVID-19 vaccination, with the aim of reducing the transmission of COVID-19. The implementation of mandatory vaccination for every citizen as determined by the government in several regulations. But everyone has the right to autonomy to determine health services for himself. This writing aims to examine and analyze patient autonomy rights related to the administration of the COVID-19 vaccine. The problems are studied through a statute approach and a conceptual approach with a doctrinal research which all legal materials are collected by means of a literature study. The results of this paper indicate that the right to autonomy can be overridden because vaccination has the objective of protecting the community. Keywords: COVID-19 Vaccination; Patient Autonomy Rights; Covid-19 Vaccination Obligations. AbstrakTerjadinya wabah Corona Virus Disease 2019 (COVID-19) menimbulkan berbagai dampak pada sektok kehidupan. Salah satu upaya yaitu pelaksanaan vaksinasi COVID-19, dengan tujuan mengurangi penularan COVID-19. Pelaksanaan vaksinasi wajib bagi setiap warga sebagaimana telah ditentukan oleh pemerintah dalam beberapa peraturan. Tetapi setiap orang memiliki hak otonomi untuk menentukan pelayanan kesehatan bagi dirinya. Penulisan ini bertujuan untuk mengkaji dan menganalisis hak otonomi pasien berkaitan dengan pemberian vaksin COVID-19 Permasalahan dikaji melalui pendekatan peraturan perundang-undangan dan pendekatan konseptual dengan metode penulisan doctrinal research dimana semua bahan hukum dikumpulkan dengan studi kepustakaan. Hasil penulisan menunjukkan bahwa hak otonomi dapat dikesampingkan dikarenakan vaksinasi memiliki tujuan untuk melindungi masyarakat.Kata Kunci: Vaksinasi COVID-19; Hak Otonomi Pasien; Kewajiban Vaksinasi Covid-19.